126k views
4 votes
Solve -4(6x + 3) = -12(x + 10)

A. x = -5
B. x = 2
C. x = 5
D. x = 9

User Tanyia
by
4.6k points

2 Answers

5 votes

Answer:

x = 0

Explanation:

-4(6x + 3) = -12(x + 10)

Distribute -4 and -12

-24x - 12 = -12x - 12

Get like terms on one side

-24x + 12x = -12 + 12

-12x = 0

x = 0

//Not sure if the problem is right

User Wil
by
4.8k points
4 votes

Answer: X = 9

Why?:

The order of operations: parentheses, exponents, multiplication, division, addition, subtraction.

-4 (6x + 3)

6 x 9 = 54

54 + 3 = 57

57 x (-4) = -228

9 + 10 = 19

19 x -12 = -228

User Domenukk
by
5.5k points